(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
ABSTRACTIn this work, surfaces of Al 6061 alloy were coated using anodizing and micro–arc oxidation ( MAO) duplex processes. MAO electrolyte was modified using ( 2-6 g/l )Al2O3 additives . X-ray diffraction (XRD), scanning electron microscopy (SEM), Vickers indenter, atomic force microscopy (AFM), and Microprocessor coating thickness meter ,were employed for characterization of the deposited coatings .Results showed that the coatings contained porous oxide ?-alumina with morphologies characterized by different levels of porosity non-uniform distribution, and their thickness and hardness increased by the increasing of Al2O3 additives. The research demonstrates that a relatively hard (421-490Hv), thick (43-65?m) and uniform coatings, can successfully be deposited on preanodized Al alloy (12-15 ?m with hardness of 190Hv) using Al2O3 additives containing MAO electrolytes as a new method for more future research on surface improvements of Al alloys.